2018
DOI: 10.1093/jscr/rjy323
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Paneth cell metaplasia in an ovarian Krukenberg tumor: report of an unusual case and literature review

Abstract: Paneth cells are classified as secretory cells which are normally found in the cecum and ascending colon. Their presence in other parts of the gastrointestinal tract is regarded as abnormal and indicates metaplasia. Paneth cells may also be rarely found in gastrointestinal, biliary and prostatic tumors. The presence of Paneth cells in ovarian Krukenberg tumors is rare and to the best of our knowledge is restricted to metastatic appendiceal goblet cells tumors. We report a rare case of unilateral metastatic gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Esophagus Conventional H&E staining Chen et al, 2015 H&E, light microscopy and electron microscopy Schreiber et al, 1978 H&E, periodic acid-Schiff/Alcian blue Takubo et al, 1995 H&E, Lendrum's Phyloxine-tartrazine stain Thompson et al, 1983 Stomach Periodic acid-Schiff/Alcian blue at pH 2.5 Abraham et al, 2003 H&E, Masson's Trichome, Lendrum's Phyloxine-tartrazine, Periodic acid-Schiff/Alcian blue at pH 2.5 and colloidal iron pH 1.9 staining Albedi et al, 1984 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5, immunostaining for lysozyme Deveci and Deveci, 2004 Immunostaining for lysozyme Gassler et al, 2002 Conventional H&E staining Inada et al, 1997 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5 and Electron microscopy Matsubara, 1977 Immunoelectron microscopy for lysozyme Ohtani and Sasano, 1988 Immunostaining for HD5 and HD6 Ostaff et al, 2015 Conventional H&E staining Rubio et al, 1987 Lysozyme immunostaining Rubio, 2012 Gallbladder Conventional H&E staining Albores-Saavedra et al, 1986 Conventional H&E staining Bae et al, 2002 Electron microscopy, H&E, Periodic acid-Schiff Laitio and Nevalainen, 1975 Conventional H&E staining Sakaki et al, 2000 Ovary Conventional H&E staining Alrajban et al, 2018 Conventional H&E staining Niemiec et al, 1989 Prostate Conventional H&E staining, immunostaining for lysozyme Frydman et al, 1992 Conventional H&E staining Adlakha and Bostwick, 1994 (Shen et al, 2005). Additionally, Paneth-like cells were reported in gastric adenomas and carcinomas (Heitz and Wegmann, 1980;Ito et al, 1986;Caruso et al, 1989;Rubio, 1989).…”
Section: Methods Of Identification Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophagus Conventional H&E staining Chen et al, 2015 H&E, light microscopy and electron microscopy Schreiber et al, 1978 H&E, periodic acid-Schiff/Alcian blue Takubo et al, 1995 H&E, Lendrum's Phyloxine-tartrazine stain Thompson et al, 1983 Stomach Periodic acid-Schiff/Alcian blue at pH 2.5 Abraham et al, 2003 H&E, Masson's Trichome, Lendrum's Phyloxine-tartrazine, Periodic acid-Schiff/Alcian blue at pH 2.5 and colloidal iron pH 1.9 staining Albedi et al, 1984 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5, immunostaining for lysozyme Deveci and Deveci, 2004 Immunostaining for lysozyme Gassler et al, 2002 Conventional H&E staining Inada et al, 1997 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5 and Electron microscopy Matsubara, 1977 Immunoelectron microscopy for lysozyme Ohtani and Sasano, 1988 Immunostaining for HD5 and HD6 Ostaff et al, 2015 Conventional H&E staining Rubio et al, 1987 Lysozyme immunostaining Rubio, 2012 Gallbladder Conventional H&E staining Albores-Saavedra et al, 1986 Conventional H&E staining Bae et al, 2002 Electron microscopy, H&E, Periodic acid-Schiff Laitio and Nevalainen, 1975 Conventional H&E staining Sakaki et al, 2000 Ovary Conventional H&E staining Alrajban et al, 2018 Conventional H&E staining Niemiec et al, 1989 Prostate Conventional H&E staining, immunostaining for lysozyme Frydman et al, 1992 Conventional H&E staining Adlakha and Bostwick, 1994 (Shen et al, 2005). Additionally, Paneth-like cells were reported in gastric adenomas and carcinomas (Heitz and Wegmann, 1980;Ito et al, 1986;Caruso et al, 1989;Rubio, 1989).…”
Section: Methods Of Identification Referencesmentioning
confidence: 99%
“…Therefore, the presence of Paneth cells could be a protective mechanism against the pathogenic bacteria in lithogenic bile. Alrajban et al (2018) reported the first PCM in Krukenberg tumors, which represents 1-2% of ovarian tumors and are characterized by the presence of metastatic adenocarcinoma cells. A poorly differentiated carcinoma was observed to contain a mixture of signet ring malignant cells with eosinophilic cytoplasm characteristic of PCM.…”
Section: Appearance Of Paneth Cells In Other Gastrointestinal and Nonmentioning
confidence: 99%
“…Ovarian metastasis occurs in approximately 5-10% with female GC and has also been reported in 33-41% of autopsies (9). KT has mostly been reported in case reports (10)(11)(12)(13), with an overall survival (OS) of less than 1 year. As described in case reports and clinical analysis, the main pathological type of KT is signet ring cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%